Augmented Reality Integration for Smart Campus Experience at USN Kolaka - Muarif, Amar; Sari, Jayanti Yusmah; Bantun, Suharsono (Media of Computer Science, 2024)
In an effort to enhance promotion at the Universitas Sembilanbelas November (USN) Kolaka, an Augmented Reality (AR) application has been developed incorporating the smart campus concept. This application is designed to provide interactive 3D visualizations of campus facilities, allowing prospective students and visitors to explore the infrastructure virtually. It has undergone extensive black box testing across various devices, demonstrating high technical reliability with key functionalities operating stably. Media expert evaluations gave an average score of 4.9, reflecting a very high level of satisfaction with its design and functionality. Moreover, a usability evaluation conducted with students noted that 80% of them rated it as excellent, describing the application as user-friendly and engaging. This success underscores the potential of AR applications in enriching campus experiences, reinforcing USN Kolaka's image as a modern and technologically adaptive educational institution, and opening opportunities for its use in broader campus promotion and marketing efforts.